(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Food security remains a critical global challenge, exacerbated by factors such as population growth, climate change, economic instability, and unequal distribution of resources. This paper provides a comprehensive review of strategies aimed at enhancing food security across different scales, from local to global levels.